Policy Formulation of Criminal Actions Related To Binary Option Through The Criminal Justice System In Indonesia - Musa Darwin Pane (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The quality of technology and increasing globalization. Currently, there is a lot of investment using the Binary Option Trading model, where this practice has not been accommodated by the laws and regulations in Indonesia and has resulted in victims who suffer losses. This study aims to identify and understand the formulation policies of Binary Option Trading in Indonesia and the enforcement of Binary Option Trading laws in Indonesia. This research method is descriptive with the type of normative juridical research, using a statutory approach and a conceptual approach. Based on the results of the study showed that both organizers, Binary Options influencers and affiliates can be subject to multiple articles as regulated in the Criminal Code, the ITE Law, the Consumer Protection Law, and the Money Laundering Law. However, in the application of legal witnesses, it is important to note that criminal sanctions are the ultimum remedium, therefore it is important to apply other sanctions such as refunding losses, so that the goal of a fair sentence can be realized. In terms of law enforcement through prevention efforts, it should be prioritized, namely law enforcers must be active by carrying out integrated efforts, considering that it is an ordinary offense, so as to prevent the emergence of victims in the future. Therefore, it is important to apply other sanctions such as refunding losses, so that the goal of a just punishment can be realized. In terms of law enforcement through prevention efforts, it should be prioritized, namely law enforcers must be active by carrying out integrated efforts, considering that it is an ordinary offense, so as to prevent the emergence of victims in the future. Therefore, it is important to apply other sanctions such as refunding losses, so that the goal of a just punishment can be realized. In terms of law enforcement through prevention efforts, it should be prioritized, namely law enforcers must be active by carrying out integrated efforts, considering that it is an ordinary offense, so as to prevent the emergence of victims in the future.